'At least I am married': Muslim–Christian marriage and gender in southwest Nigeria. (21st April 2020) - Nolte, Insa
Abstract : This article explores religious coexistence among the Yoruba of southwest Nigeria. It focuses on interfaith marriages, frequent especially between Muslim men and Christian women, as a practice that brings Islam and Christianity into a mutually productive relationship. The article explores the tension between the general understanding that interfaith marriage is a positive anchor of Muslim–Christian relations and the widespread individual scepticism towards such marriages. Rooted in distinct discourses, Muslim and Christian attitudes to interfaith marriage have undergone changes along different trajectories since the 1980s. At the same time, they share a 'family resemblance' because members of both religions emphasise the importance of marriage and its unequally gendered nature. The unequal and asymmetric relationships between the two religions constitute part of a wider religious field, where the shared belief in the importance of conjugality is central to the gendered social order. Thus, even though Muslim–Christian marriages are often understood as problematic, they are still seen as less problematic than the failure to marry. « Au moins, je suis marié » : le mariage entre musulmans et chrétiens et le genre dans le sud‐ouest du Nigéria: Cet article se penche sur la coexistence religieuse chez les Yorubas au sud‐ouest du Nigéria. Il se concentre sur les mariages interconfessionnels, particulièrement fréquents entre hommes musulmans et femmes chrétiennes, en tant que pratique établissant une relation réciproquement productive entre l'Islam et le Christianisme. L'article examine la tension entre la conception générale, selon laquelle le mariage interconfessionnel est un pilier bénéfique pour les relations entre musulmans et chrétiens, et le scepticisme individuel largement répandu à l'égard de ces mariages. Prenant racine dans des discours distincts, les attitudes des musulmans et des chrétiens à l'égard du mariage interconfessionnel évoluent le long de trajectoires différentes depuis les années 1980. Elles ont en même temps un « air de famille », car les membres des deux religions insistent sur l'importance du mariage et sur sa nature inégalement genrée. Les relations inégales et asymétriques entre les deux religions s'inscrivent dans un champ religieux plus large, dans lequel la croyance commune en l'importance de la conjugalité est au cœur de l'ordre social genré. Ainsi, les mariages entre musulmans et chrétiens sont souvent considérés comme problématiques, mais moins que l'absence de mariage.